Phototreatment of Palm Oil Mill Effluent (POME) over Cu/TiO2 Photocatalyst - Cheng, C. K.; Kim, Hoong Ng; Mohd Rizauddin, Deraman; Chun, How Ang; Soo, Kee Chong; Kong, Zi Ying; Khan, Maksudur R. (Department of Chemical Engineering, Diponegoro University, 2014)
The current work reported on the use of different formulations of Cu/TiO2 photocatalysts for the UV-irradiation of palm oil mills effluent (POME). Different copper loadings, viz. 2 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt% and 25 wt% were doped onto titania. XRD pattern confirmed the presence of anatase TiO2 as primary phase due to mild calcination temperature (573 K). Photo-decomposition of POME over 20 wt% Cu/TiO2 exhibited the highest conversion (27.0%) attributed to its large pore diameter (20.0 nm). In addition, optimum loading was 0.83 g/l.